2013
DOI: 10.5402/2013/958945
|View full text |Cite
|
Sign up to set email alerts
|

Better Rooting Procedure to Enhance Survival Rate of Field Grown Malaysian Eksotika Papaya Transformed with 1-Aminocyclopropane-1-Carboxylic Acid Oxidase Gene

Abstract: A high survival rate for transformed papaya plants when transferred to the field is useful in the quest for improving the commercial quality traits. We report in this paper an improved rooting method for the production of transformed Malaysian Eksotika papaya with high survival rate when transferred to the field. Shoots were regenerated from embryogenic calli transformed with antisense and RNAi constructs of 1-aminocyclopropane-1-carboxylic acid oxidase (ACO) genes using the Agrobacterium tumefaciens-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The phenomenon of callus formation at the base of the shoots is very common in papayas, and it inhibits the complete germination of somatic embryos. Indeed, it has been previously reported in babaco (Vega de Rojas and Kitto, ) and C. papaya (Ascencio‐Cabral et al., ; Sekeli et al., ; Dhekney et al., ; Posada‐Pérez et al., ). Recently, Posada‐Pérez et al.…”
Section: Discussionmentioning
confidence: 80%
“…The phenomenon of callus formation at the base of the shoots is very common in papayas, and it inhibits the complete germination of somatic embryos. Indeed, it has been previously reported in babaco (Vega de Rojas and Kitto, ) and C. papaya (Ascencio‐Cabral et al., ; Sekeli et al., ; Dhekney et al., ; Posada‐Pérez et al., ). Recently, Posada‐Pérez et al.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, different hormonal combinations are fundamental to find the most adequate conditions to promote efficient rhizogenesis and, consequently, to allow better performance of regenerated plants in the acclimatization phase. In this scenario, several authors observed the superior effect of IBA in relation to the other auxins used in the in vitro rooting of papaya buds (TEIXEIRA DA SILVA et al, 2007, KUMAR et al, 2012, NZILANI et al, 2013SEKELI Et al., 2013). In this context, in addition to the hormonal stimuli and other components of the culture medium, an alternative to increase efficiency in the acclimatization conditions is to allow in vitro gas exchanges, promoting greater ventilation of gases produced during the stretching and rooting phases (LAI et al ., 1998).…”
Section: Organogenesismentioning
confidence: 97%
“…This behaviour is good evidence of the effectiveness of the culture conditions and zeolite as a substrate, ventilation of the culture vessels, IBA as a rooting inducer, and the absence of sucrose probably favored the source-demand effect so that photoautotroph would enhance the rooting stimulus of auxin. Several authors note the superior effect that IBA has with respect to other auxins for rooting of in vitro shoots in papaya (Yu et al, 2000;Teixeira da Silva et al, 2007;Kumar et al, 2012;Nzilani et al, 2013;Sekeli et al, 2013). These last authors reported that the best results in the rooting of in vitro shoots of transgenic papaya, Eksotika variety were achieved when first placing the shoots in culture medium with 9.8 µM IBA and in darkness for 4 days and thereafter were subcultured on MS culture medium at 50% of salt concentration, 10 µM of riboflavin and vermiculite as support.…”
Section: Effects Of Sucrose and Auxin On Rooting And In Vitro Acclimamentioning
confidence: 99%
“…(Afreen- Zobayed et al, 1999); Eucalyptus sp. (Zobayed et al, 2001); four Australian papaya varieties (Kaity et al, 2009) and in the variety Eksotika (Sekeli et al, 2013); Orchid (Doritaenopsis sp.) (Shin et al, 2013) using different types of porous materials (vermiculite, perlite and mixtures of both).…”
Section: Effects Of Sucrose and Auxin On Rooting And In Vitro Acclimamentioning
confidence: 99%
See 1 more Smart Citation